Dinamika Pengaturan Tanah Adat di Kota Medan dalam Perspektif Hukum Agraria Kontemporer - Tri Reni Novita; Juradhanie Shera Tanjung; Nurhayati Nasution; Hariaty Panggabean (Lembaga Yasin AlSys, 2026)
Customary land has an important position for customary law communities because it functions not only as an economic resource but also contains social, cultural, and historical values embedded in community life. In Medan City, urban development, investment, and land-use conversion have created issues related to the existence of and legal protection for customary land, including agrarian conflicts, overlapping land control, and weak legal certainty for customary communities. This study aims to analyze the dynamics of customary land regulation in Medan City from the perspective of contemporary agrarian law, with an emphasis on aspects of recognition, legal protection, and policy implementation. This study used a normative legal method with statutory, conceptual, and historical approaches. The results showed that although customary communal rights have been recognized in the national agrarian legal system, their implementation at the local level still faces various obstacles, such as discrepancies between legal norms and field practices, overlapping land control, and limited legal certainty for customary communities in urban areas. Recent policies related to the registration of customary communal land provide opportunities to strengthen legal protection, but their implementation still faces administrative and institutional challenges. In addition, urban development, increased economic activity, and investment flows in Medan City also exert pressure on the existence of customary land, which has the potential to trigger agrarian conflicts. The conclusion of this study emphasizes the need for a comprehensive, adaptive, and sustainable agrarian law approach to realize fairer and more responsive protection of customary communal rights amid urban dynamics. The implications of this study indicate the importance of synergy among the government, customary communities, and stakeholders in strengthening recognition, protection, and legal certainty over customary land in Medan City.